The population structure and recent colonization history of O regon threespine stickleback determined using restriction‐site associated DNA ‐sequencing - Julian Catchen; Susan Bassham; Taylor Wilson; Mark Currey; Conor O'Brien; Quick Yeates; William A. Cresko (Molecular Ecology, 2013)
Understanding how genetic variation is partitioned across genomes within and among populations is a fundamental problem in ecological and evolutionary genetics. To address this problem, we studied the threespine stickleback fish, which has repeatedly undergone parallel phenotypic and genetic differentiation when oceanic fish have invaded freshwater habitats. While significant evolutionary genetic research has been performed using stickleback from geographic regions that have been deglaciated in the last 20 000 years, less research has focused on freshwater populations that predate the last glacial maximum. We performed restriction‐site associated DNA ‐sequencing ( RAD ‐seq) based population genomic analyses on stickleback from across O regon, which was not glaciated during the last maximum. We sampled stickleback from coastal, Willamette Basin and central O regon sites, analysed their genetic diversity using RAD ‐seq, performed structure analyses, reconstructed their phylogeographic history and tested the hypothesis of recent stickleback introduction into central O regon, where incidence of this species was only recently documented. Our results showed a clear phylogeographic break between coastal and inland populations, with oceanic populations exhibiting the lowest levels of divergence from one another. Willamette Basin and central Oregon populations formed a clade of closely related populations, a finding consistent with a recent introduction of stickleback into central Oregon. Finally, genome‐wide analysis of genetic diversity (π) and correlations of alleles within individuals in subpopulations ( F IS ) supported a role for introgressive hybridization in coastal populations and a recent expansion in central Oregon. Our results exhibit the power of next‐generation sequencing genomic approaches such as RAD ‐seq to identify both historical population structure and recent colonization history.